Development of a modified thermal humidity index and its application to human thermal comfort of urban vegetation patches - Xiaorou Zheng; Na Zhang; Xin Wang (Ecosystem Health and Sustainability, 2022)
Extremely hot environments can trigger serious health problems. To evaluate the effects of microclimate on thermal comfort, we proposed and validated a modified thermal humidity index (MTHI) that combined air temperature and relative humidity with land surface temperature (LST). MTHI was more sensitive to microclimate changes than the general thermal humidity index that includes only T and RH, and thus the thermal comfort could be better indicated. In an urban riparian buffer study, we estimated the temporal dynamics and spatial distribution of MTHI values for 47 vegetation patches and explored how structural characteristics of patches affect the thermal comfort. The results showed that planting could significantly reduce LST and MTHI. Vegetation patches with complex vertical structures had considerably higher thermal comfort than those with simple structures. Decreasing nearest distance to river or increasing plant abundance could reduce the thermal discomfort. There were significant differences in the structure characteristics between the patches with MTHI <70 and those with MTHI >70, implying the critical thresholds of variations in thermal comfort with patch structure. Given that people always feel uncomfortable during the daytime in July, optimizing the patch structure is essential to improve the microclimate regulation services of an urban landscape.